Pitch Accuracy in the Singing of Secondary School Students - Su, Lih Huey (2008)

(untitled)
The objective of the study was to determine the pitch accuracy in the singing of secondary students, in various tonal pattern setting via quantitative approach. In order to determine whether certain tonal patterns predict greater pitch accuracy in contrasting song material, this study analyses the sung pitch fundamental frequencies of the secondary school students. The tonal patterns covered in this study are phrases form national anthem Negaraku, Rasa Sayang, and Auld Lang Syne; put in the progression of ascending, and descending; and are derived from music materials that are familiar to the respondents. The subjects for the study (N = 92) were secondary students of Chong Hwa Independent High School, where 45 (aged 16-18) were upper form students and another 47 (aged 13- 15) were lower form students. A pitch model in PowerPoint instructions was prepared. Respondents were asked to sing four test patterns guided by the PowerPoint instructions. Test patterns consist of combination of the four variables of diatonic major, pentatonic, ascending, and descending, constructed into 19 pitches in total. Therefore, 1748 sung pitches would be subjected to quantitative evaluation. Recording of singing was edited using Adobe Audition audio editing software, and pitches was analysed according to the Target Pitch Frequency, based on equal temperament. For measurement analysis, the Praat software was used to determine the fundamental frequencies from the waveforms of the recorded data. Research result reveals that upper form students sang with lesser pitch accuracy compared to lower form students. The junior high male and female, and senior high male students sang average accurately on all the test patterns except senior high female was unable to sing the pitches in tune. Besides, students sang with greater pitch accuracy when they sang an ascending pattern in diatonic scale. Result also revealed that the descending patterns in diatonic scale were less accurate than in pentatonic scale. 63% of the respondents were found with an average pitch deviation of 25 cents and below, categorized as accurate singers while 17% of the respondents were with an average pitch deviation of 100 cents (one semitone) and above and were categorized as inaccurate singers. Future studies may look into the relationship of vocal parameters and pitch accuracy through quantitative evaluation.